2020
DOI: 10.1136/rapm-2019-100875
|View full text |Cite
|
Sign up to set email alerts
|

Levo-corydalmine attenuates microglia activation and neuropathic pain by suppressing ASK1-p38 MAPK/NF-κB signaling pathways in rat spinal cord

Abstract: Background and objectivesNeuropathic pain is partially refractory to currently available treatments. Although some studies have reported that apoptosis signal-regulating kinase 1 (ASK1) may inhibit chronic pain, the mechanisms underlying this process have not been fully elucidated.MethodsChronic constriction injury (CCI) of the rat sciatic nerve was used to establish a neuropathic pain model. Nociception was assessed using von Frey hair and Hargreaves’ methods. Western blot and immunofluorescence were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Nuclear factor-kappa B (NF- κ B) is a widely studied transcription factor that is involved in many physiological processes, such as regulating multiple aspects of innate and adaptive immune function [ 17 , 18 ], and as a key mediator of the inflammatory response in regulating inflammatory pain [ 19 ], neuropathic pain [ 20 ], and other chronic pain [ 21 ]. Recent studies have shown that NF- κ B participates in the inflammatory cascade by activating the Nod-like receptor protein 3 (NLRP3) inflammasome in the nucleus [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor-kappa B (NF- κ B) is a widely studied transcription factor that is involved in many physiological processes, such as regulating multiple aspects of innate and adaptive immune function [ 17 , 18 ], and as a key mediator of the inflammatory response in regulating inflammatory pain [ 19 ], neuropathic pain [ 20 ], and other chronic pain [ 21 ]. Recent studies have shown that NF- κ B participates in the inflammatory cascade by activating the Nod-like receptor protein 3 (NLRP3) inflammasome in the nucleus [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have shown that the activation of microglial cells is a key factor in the generation and persistence of neuropathic pain. 34,40 Adenosine triphosphate (ATP) is a transmitter involved in the modulation of traumatic information in the spinal cord. The damaged tissue cells and sensory nerve endings can release a large amount of ATP after peripheral nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ERK and JNK are mainly expressed in neurons and astrocytes, and p38 MAPK is mainly expressed in microglia [ 34 ]. Previous studies illustrated that the activation of microglia further acts on neurons and astrocytes by promoting secretion of proinflammatory factors [ 35 ]. Our findings also displayed that conditioned media from LPS-treated BV-2 cells significantly weakened the viability of SH-SY5Y cells, while the decline was reversed after the Mog treatment.…”
Section: Discussionmentioning
confidence: 99%